A one-generation reproductive toxicity study of the mycotoxin ochratoxin A in Fischer rats. (July 2021) - Bondy, G.S.; Curran, I.H.C.; Coady, L.C.; Armstrong, C.; Bourque, C.; Bugiel, S.; Caldwell, D.; Kwong, K.; Lefebvre, D.E.; Maurice, C.; Marchetti, F.; Pantazopoulos, P.P.; et al.
Abstract: Ochratoxin A (OTA) is a mycotoxin produced by Aspergillus and Penicillium molds. Grain-based foods account for most human dietary exposures to OTA. OTA is a teratogen, but its reproductive and developmental effects are poorly understood. A one-generation reproductive toxicity study was conducted with groups of 16 male and 16 female Fischer rats exposed to 0, 0.026, 0.064, 0.16, 0.4 or 1.0 mg OTA/kg in diet. Dams exposed to 1.0 mg OTA/kg diet had statistically significant F1 pup losses between implantation and postnatal day (PND 4). Delays in preputial separation (PPS) and vaginal opening (VO) were indicative of delayed puberty in F1 rats. Mild renal lesions in nursing pups indicated that exposure prior to weaning impacted the kidneys. The developing kidney was more susceptible to OTA than the adult kidney. Significant increases in multi-oocyte follicles (MOFs) and proportional changes in resting and growing follicles were observed in F1 female ovaries. Plasma testosterone was reduced in F0 males, and there were negative effects on sperm quality in F0 and F1 male rats. The results confirm that continuous dietary exposure to OTA causes post-implantation fetotoxicity in dams, and renal and reproductive toxicity in their male and female offspring. Highlights: Gestational exposure to OTA caused pre-implantation fetotoxicity in female rats. Dietary exposure to OTA adversely affected sperm motility in adult male rats. OTA delayed puberty in juvenile male and female rats. Developmental OTA exposure A adversely affected ovarian follicle populations. OTA caused kidney toxicity in nursing and weaned juvenile rats.